High-performance wear-resistant POM composite material and preparation method thereof

Modified resin is prepared by reacting isophorone diisocyanate, polyethylene glycol and dopamine in POM composite materials, and mixed with basalt fibers and polyformaldehyde, which solves the problem of low impact toughness of POM composite materials, and realizes a high-performance wear-resistant POM composite material.

CN119708750APending Publication Date: 2025-03-28SHENZHEN FUHENG PLASTICS PIGMENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979474.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

At this stage, the notched impact toughness of POM composites is low and is easily damaged when impacted.

Method used

Prepolymers are prepared by reactions of isophorone diisocyanate, polyethylene glycol and dopamine, and reacted with substances such as 4-formylphenylboric acid, 5A molecular sieve and ethylenediamine to form modified prepolymers and modified polyurethanes. Subsequently, γ-aminopropyltriethoxysilane and aminolated silicone were added to obtain a modifier and a modified resin. Finally, the modified resin was mixed with basalt fibers and polyformaldehyde, extruded through a twin screw and soaked in water to make a high-performance wear-resistant POM composite material.

Benefits of technology

It significantly improves the impact resistance and toughness of POM composite materials, and enhances the mechanical strength and wear resistance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-performance wear-resistant POM composite material and a preparation method thereof, modified resin and polyformaldehyde are subjected to melt extrusion, soaked in water and cooled, the POM composite material is prepared, modified resin molecules are dendritic-star polymers, and a dendritic multi-arm structure can effectively disperse stress when the composite material is subjected to external force, so that the wear resistance of the composite material is improved, and the wear resistance of the composite material is improved. Stress concentration in the composite material is reduced, the impact resistance of the composite material is improved, the elastic modulus of the composite material can be increased through a central cross-linking point, meanwhile, the cross-linking points can serve as physical cross-linking points to help to absorb and disperse external force and increase the toughness of the material, and the dendritic multi-arm side chain is a polyurethane elastomer, so that the impact resistance of the composite material is improved. A molecular chain contains boric acid ester bonds, so that the toughness and the impact resistance of the composite material can be further improved, and when the composite material is soaked in water, siloxane in modified resin molecules can be hydrolyzed and crosslinked, so that the crosslinking degree is slightly increased, and the mechanical strength of the composite material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of POM composite material preparation, and in particular to a high-performance wear-resistant POM composite material and a preparation method thereof. Background Art

[0002] Polyoxymethylene (POM) is a linear thermoplastic polymer with only repeated -CH2O- links in its main molecular chain, regular molecular structure and high crystallinity. As one of the five major engineering plastics, POM has excellent comprehensive performance, excellent mechanical properties, friction properties, chemical resistance and creep resistance, especially outstanding wear resistance and good self-lubrication. It is one of the plastic varieties with specific strength and specific stiffness close to metal. POM can be used as a substitute for metal and alloy materials. POM is widely used in the fields of machinery industry, automotive parts, electronic appliances, daily consumer goods and medical equipment. However, polyoxymethylene itself has disadvantages such as low notch impact toughness and notch impact sensitivity, which makes the material brightness significantly reduced after a notch appears, resulting in inability to use normally. Summary of the invention

[0003] The purpose of the present invention is to provide a high-performance wear-resistant POM composite material and a preparation method thereof, which solves the problem that the current POM composite material has low notch impact toughness and is easily damaged when impacted.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a high-performance wear-resistant POM composite material comprises the following steps:

[0006] Step A1: isophorone diisocyanate, polyethylene glycol and DMF are mixed, stirred and dibutyltin dilaurate is added at a speed of 120-150 r / min and a temperature of 65-75° C., and the mixture is reacted for 2-3 hours, dopamine is added, and the reaction is continued for 2-3 hours to obtain a prepolymer, and the prepolymer, 4-formylphenylboronic acid, 5A molecular sieve and DMF are uniformly mixed, and the mixture is reacted at a speed of 150-200 r / min and a temperature of 60-65° C. for 10-15 hours to obtain a modified prepolymer;

[0007] Step A2: The modified prepolymer, ethylenediamine, p-toluenesulfonic acid and DMF are mixed, and the mixture is reacted for 3-5 hours at a speed of 200-300 r / min and a temperature of 50-60° C. to obtain a modified polyurethane; the modified polyurethane, β-cyclodextrin and DMF are mixed, and the mixture is stirred for 3-5 hours at a speed of 200-300 r / min and a temperature of 70-80° C., and then allowed to stand for 10-15 hours to obtain an inclusion polyurethane; isophorone diisocyanate, inclusion polyurethane and DMF are mixed, and the mixture is reacted for 3-5 hours at a speed of 120-150 r / min and a temperature of 65-75° C.; γ-aminopropyltriethoxysilane is added, and the mixture is reacted for 4-6 hours to obtain a modifier;

[0008] Step A3: The modifier, amino silicone and DMF are mixed, and reacted for 3-5 hours at a rotation speed of 200-300 r / min and a temperature of 50-60° C. to obtain a modified resin. The modified resin, basalt fiber and polyoxymethylene are mixed and added to a twin-screw extruder, and extruded at a rotation speed of 100-200 r / min and a temperature of 175-180° C. and immersed in water for cooling to obtain a POM composite material.

[0009] Furthermore, the molar ratio of isophorone diisocyanate, polyethylene glycol and dopamine in step A1 is 3:4:2, and the usage ratio of prepolymer, 4-formylphenylboronic acid and 5A molecular sieve is 15mmol:30mmol:4g.

[0010] Furthermore, the molar ratio of the modified prepolymer and ethylenediamine described in step A2 is 1:2, the amount of p-toluenesulfonic acid used is 1.5‰ of the mass of the modified prepolymer, the amount ratio of modified polyurethane, β-cyclodextrin and DMF is 1g:1g:10mL, and the molar ratio of isophorone diisocyanate, inclusion polyurethane and γ-aminopropyltriethoxysilane is n+1:n:1, where n is a natural number greater than 0.

[0011] Furthermore, the molar ratio of the modifier described in step A3 to the amino silicone is 14:1, the mass ratio of the modified resin, basalt fiber and polyoxymethylene is 1:1:10, and the model of the basalt fiber is.

[0012] Furthermore, the amino silicone is prepared by the following steps:

[0013] Step B1: Tetrahydrofuran, sodium hydroxide and deionized water are mixed uniformly, stirred and phenyltrimethoxysilane is added at a speed of 120-150 r / min and a temperature of 65-70° C., and reacted for 5-6 hours, then tetrahydrofuran is removed, the substrate is dissolved in methanol, and acetic acid is added for neutralization to obtain an intermediate, and the intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane are mixed uniformly, and reacted at a speed of 60-80 r / min and a temperature of 15-20° C. for 20-25 hours to obtain a capping agent;

[0014] Step B2: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, a capping agent, chloroplatinic acid and DMF are mixed uniformly, and the reaction is carried out for 3-5 hours at a speed of 150-200 r / min and a temperature of 80-90° C. to obtain modified silicone;

[0015] Step B3: Dissolve the modified organosilicon in DMF, stir and add mixed acid at a speed of 60-80r / min and a temperature of 3-5°C, react for 1-2h, adjust the pH value to neutral, and obtain nitroorganosilicon; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add nitroorganosilicon at a speed of 150-200r / min and a temperature of 80-85°C, and react for 3-5h to obtain aminoorganosilicon.

[0016] Furthermore, the amount ratio of tetrahydrofuran, sodium hydroxide, deionized water and phenyltrimethoxysilane in step B1 is 200mL:70mmo l:3.5g:130mmo l, and the amount ratio of the intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane is 1mmo l:1mL:1mmo l.

[0017] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane in step B2 is 2.4:2:3, the molar ratio of dihydrogenpolysiloxane and the capping agent is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of dihydrogenpolysiloxane.

[0018] Furthermore, the dosage ratio of the modified silicone and the mixed acid described in step B3 is 1g:6mL, the mixed acid is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 11:7, and the dosage ratio of zinc powder, ammonium chloride, deionized water, DMF and nitrosilicone is 2.5g:1g:20mL:50mL:1.5g.

[0019] The beneficial effects of the present invention are as follows: a high-performance wear-resistant POM composite material disclosed by the present invention is prepared by reacting isophorone diisocyanate with polyethylene glycol, and then end-capping with dopamine to obtain a prepolymer; the prepolymer is reacted with 4-formylphenylboronic acid so that the catechol on the prepolymer reacts with the boric acid group on the 4-formylphenylboronic acid to obtain a modified prepolymer; the modified prepolymer is reacted with ethylenediamine so that the aldehyde group on the modified prepolymer reacts with the amino group on the ethylenediamine to form an amino end-capping to obtain a modified polyurethane; the modified polyurethane is blended with β-cyclodextrin to form a β-cyclodextrin inclusion modified polyurethane molecular structure to obtain an inclusion polyurethane; isophorone diisocyanate is reacted with the inclusion polyurethane, and then single-end end-capping is performed with γ-aminopropyltriethoxysilane to obtain a modifier; the modifier is reacted with amino silicone to obtain a modified resin; the modified resin and polyoxymethylene are melt-extruded and immersed in water for cooling to obtain a POM composite material.

[0020] The amino silicone is prepared by hydrolyzing and condensing phenyltrimethoxysilane as a raw material to form a semi-closed cage-type silsesquioxane to obtain an intermediate, condensing the intermediate with γ-methacryloxypropyltrimethoxysilane to close the ring to obtain a capping agent, opening the ring of octamethylcyclotetrasiloxane and then condensing it with tetramethyldisiloxane to obtain dihydrogenpolysiloxane, reacting the dihydrogenpolysiloxane with the capping agent to make the Si-H bond on the dihydrogenpolysiloxane react with the double bond on the capping agent to obtain modified silicone, treating the modified silicone with a mixed acid to make the nitro group grafted to the para position of the benzene ring to obtain nitrated silicone, and reducing the nitrated silicone with zinc powder to convert the nitro group into an amino group to obtain amino silicone.

[0021] The modified resin molecules are dendritic-star polymers. The dendritic multi-arm structure can effectively disperse stress when the composite material is subjected to external force, thereby reducing stress concentration inside the composite material and improving the impact resistance of the composite material. The central cross-linking point can increase the elastic modulus of the composite material. At the same time, these cross-linking points can serve as physical cross-linking points to help absorb and disperse external forces and increase the toughness of the material. The dendritic multi-arm side chains are polyurethane elastomers with borate bonds on the molecular chains and polyrotaxane structures on the side chains, which can further enhance the toughness and impact resistance of the composite material. When immersed in water, the siloxane in the modified resin molecules will undergo hydrolysis and cross-linking, thereby slightly increasing the degree of cross-linking, thereby further enhancing the mechanical strength of the composite material. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1: A method for preparing a high-performance wear-resistant POM composite material, comprising the following steps:

[0024] Step A1: isophorone diisocyanate, polyethylene glycol and DMF are mixed, stirred and dibutyltin dilaurate is added at a speed of 120 r / min and a temperature of 65° C., and the mixture is reacted for 2 hours. Dopamine is added and the reaction is continued for 2 hours to obtain a prepolymer. The prepolymer, 4-formylphenylboronic acid, 5A molecular sieve and DMF are uniformly mixed, and the mixture is reacted at a speed of 150 r / min and a temperature of 60° C. for 10 hours to obtain a modified prepolymer;

[0025] Step A2: The modified prepolymer, ethylenediamine, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out for 3 hours at a speed of 200 r / min and a temperature of 50° C. to obtain a modified polyurethane; the modified polyurethane, β-cyclodextrin and DMF are mixed, and the mixture is stirred for 3 hours at a speed of 200 r / min and a temperature of 70° C., and then allowed to stand for 10 hours to obtain an inclusion polyurethane; isophorone diisocyanate, inclusion polyurethane and DMF are mixed, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 65° C.; γ-aminopropyltriethoxysilane is added, and the mixture is reacted for 4 hours to obtain a modifier;

[0026] Step A3: The modifier, amino silicone and DMF are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 50°C for 3 hours to obtain a modified resin. The modified resin, basalt fiber and polyoxymethylene are mixed and added to a twin-screw extruder, and extruded at a speed of 100 r / min and a temperature of 175°C and immersed in water for cooling to obtain a POM composite material.

[0027] The molar ratio of isophorone diisocyanate, polyethylene glycol and dopamine in step A1 is 3:4:2, the molecular weight of polyethylene glycol is 1000, the amount ratio of prepolymer, 4-formylphenylboronic acid and 5A molecular sieve is 15mmo l:30mmo l:4g, and the model of polyoxymethylene is BS090.

[0028] The molar ratio of the modified prepolymer and ethylenediamine described in step A2 is 1:2, the amount of p-toluenesulfonic acid used is 1.5‰ of the mass of the modified prepolymer, the amount ratio of modified polyurethane, β-cyclodextrin and DMF is 1g:1g:10mL, and the molar ratio of isophorone diisocyanate, inclusion polyurethane and γ-aminopropyltriethoxysilane is 2:1:1.

[0029] The molar ratio of the modifier and the amino silicone described in step A3 is 14:1, and the mass ratio of the modified resin, the basalt fiber and the polyoxymethylene is 1:1:10.

[0030] The amino silicone is prepared by the following steps:

[0031] Step B1: Tetrahydrofuran, sodium hydroxide and deionized water are mixed uniformly, stirred and phenyltrimethoxysilane is added at a speed of 120 r / min and a temperature of 65° C., and reacted for 5 hours, then tetrahydrofuran is removed, the substrate is dissolved in methanol, and acetic acid is added for neutralization to obtain an intermediate, and the intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane are mixed uniformly, and reacted at a speed of 60 r / min and a temperature of 15° C. for 20 hours to obtain a capping agent;

[0032] Step B2: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 105° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, a capping agent, chloroplatinic acid and DMF are mixed uniformly, and the reaction is carried out for 3 hours at a speed of 150 r / min and a temperature of 80° C. to obtain modified silicone;

[0033] Step B3: Dissolve the modified organosilicon in DMF, stir and add mixed acid at a speed of 60 r / min and a temperature of 3°C, react for 1 hour, adjust the pH value to neutral, and obtain nitroorganosilicon; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add nitroorganosilicon at a speed of 150 r / min and a temperature of 80°C, and react for 3 hours to obtain aminoorganosilicon.

[0034] The amount ratio of tetrahydrofuran, sodium hydroxide, deionized water and phenyltrimethoxysilane in step B1 is 200mL:70mmo l:3.5g:130mmo l, and the amount ratio of intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane is 1mmo l:1mL:1mmo l.

[0035] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step B2 is 2.4:2:3, the molar ratio of dihydrogenpolysiloxane and the capping agent is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of dihydrogenpolysiloxane.

[0036] The amount ratio of the modified silicone and the mixed acid described in step B3 is 1g:6mL, the mixed acid is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 11:7, and the amount ratio of zinc powder, ammonium chloride, deionized water, DMF and nitro silicone is 2.5g:1g:20mL:50mL:1.5g.

[0037] Embodiment 2: A method for preparing a high-performance wear-resistant POM composite material, comprising the following steps:

[0038] Step A1: isophorone diisocyanate, polyethylene glycol and DMF are mixed, stirred and dibutyltin dilaurate is added at a speed of 120 r / min and a temperature of 70° C., and the mixture is reacted for 2 hours. Dopamine is then added and the reaction is continued for 3 hours to obtain a prepolymer. The prepolymer, 4-formylphenylboronic acid, 5A molecular sieve and DMF are uniformly mixed, and the mixture is reacted at a speed of 150 r / min and a temperature of 65° C. for 13 hours to obtain a modified prepolymer.

[0039] Step A2: The modified prepolymer, ethylenediamine, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 55° C. for 4 hours to obtain a modified polyurethane; the modified polyurethane, β-cyclodextrin and DMF are mixed, and the mixture is stirred at a speed of 200 r / min and a temperature of 75° C. for 4 hours, and then allowed to stand for 13 hours to obtain an inclusion polyurethane; isophorone diisocyanate, inclusion polyurethane and DMF are mixed, and the reaction is carried out at a speed of 120 r / min and a temperature of 70° C. for 4 hours, and γ-aminopropyltriethoxysilane is added and the mixture is reacted for 5 hours to obtain a modifier;

[0040] Step A3: The modifier, amino silicone and DMF are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 55°C for 4 hours to obtain a modified resin. The modified resin, basalt fiber and polyoxymethylene are mixed and added to a twin-screw extruder, and extruded at a speed of 200 r / min and a temperature of 175°C and immersed in water for cooling to obtain a POM composite material.

[0041] The molar ratio of isophorone diisocyanate, polyethylene glycol and dopamine in step A1 is 3:4:2, the molecular weight of polyethylene glycol is 1000, the amount ratio of prepolymer, 4-formylphenylboronic acid and 5A molecular sieve is 15mmo l:30mmo l:4g, and the model of polyoxymethylene is BS090.

[0042] The molar ratio of the modified prepolymer and ethylenediamine described in step A2 is 1:2, the amount of p-toluenesulfonic acid used is 1.5‰ of the mass of the modified prepolymer, the amount ratio of modified polyurethane, β-cyclodextrin and DMF is 1g:1g:10mL, and the molar ratio of isophorone diisocyanate, inclusion polyurethane and γ-aminopropyltriethoxysilane is 3:2:1.

[0043] The molar ratio of the modifier and the amino silicone described in step A3 is 14:1, and the mass ratio of the modified resin, the basalt fiber and the polyoxymethylene is 1:1:10.

[0044] The amino silicone is prepared by the following steps:

[0045] Step B1: Tetrahydrofuran, sodium hydroxide and deionized water are mixed uniformly, stirred and phenyltrimethoxysilane is added at a speed of 120 r / min and a temperature of 70° C., and reacted for 5 hours, then tetrahydrofuran is removed, the substrate is dissolved in methanol, and acetic acid is added for neutralization to obtain an intermediate, and the intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane are mixed uniformly, and reacted at a speed of 60 r / min and a temperature of 20° C. for 20 hours to obtain a capping agent;

[0046] Step B2: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 150 r / min and a temperature of 105° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, a capping agent, chloroplatinic acid and DMF are mixed uniformly, and the reaction is carried out for 4 hours at a speed of 150 r / min and a temperature of 85° C. to obtain modified silicone;

[0047] Step B3: Dissolve the modified organosilicon in DMF, stir and add mixed acid at a speed of 60 r / min and a temperature of 4°C, react for 2 hours, adjust the pH value to neutral, and obtain nitroorganosilicon; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add nitroorganosilicon at a speed of 150 r / min and a temperature of 85°C, and react for 4 hours to obtain aminoorganosilicon.

[0048] The amount ratio of tetrahydrofuran, sodium hydroxide, deionized water and phenyltrimethoxysilane in step B1 is 200mL:70mmo l:3.5g:130mmo l, and the amount ratio of intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane is 1mmo l:1mL:1mmo l.

[0049] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step B2 is 2.4:2:3, the molar ratio of dihydrogenpolysiloxane and the capping agent is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of dihydrogenpolysiloxane.

[0050] The amount ratio of the modified silicone and the mixed acid described in step B3 is 1g:6mL, the mixed acid is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 11:7, and the amount ratio of zinc powder, ammonium chloride, deionized water, DMF and nitro silicone is 2.5g:1g:20mL:50mL:1.5g.

[0051] Embodiment 3: A method for preparing a high-performance wear-resistant POM composite material, comprising the following steps:

[0052] Step A1: isophorone diisocyanate, polyethylene glycol and DMF are mixed, stirred and dibutyltin dilaurate is added at a speed of 150 r / min and a temperature of 75° C., and the mixture is reacted for 3 hours. Dopamine is then added and the mixture is reacted for 3 hours to obtain a prepolymer. The prepolymer, 4-formylphenylboronic acid, 5A molecular sieve and DMF are uniformly mixed, and the mixture is reacted at a speed of 200 r / min and a temperature of 65° C. for 15 hours to obtain a modified prepolymer.

[0053] Step A2: The modified prepolymer, ethylenediamine, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out at a speed of 300 r / min and a temperature of 60° C. for 5 hours to obtain a modified polyurethane; the modified polyurethane, β-cyclodextrin and DMF are mixed, and the mixture is stirred at a speed of 300 r / min and a temperature of 80° C. for 5 hours, and then allowed to stand for 15 hours to obtain an inclusion polyurethane; isophorone diisocyanate, inclusion polyurethane and DMF are mixed, and the reaction is carried out at a speed of 150 r / min and a temperature of 75° C. for 5 hours, and γ-aminopropyltriethoxysilane is added and the mixture is reacted for 6 hours to obtain a modifier;

[0054] Step A3: The modifier, amino silicone and DMF are mixed, and the reaction is carried out at a speed of 300 r / min and a temperature of 60°C for 5 hours to obtain a modified resin. The modified resin, basalt fiber and polyoxymethylene are mixed and added to a twin-screw extruder, and extruded at a speed of 200 r / min and a temperature of 180°C and immersed in water for cooling to obtain a POM composite material.

[0055] The molar ratio of isophorone diisocyanate, polyethylene glycol and dopamine in step A1 is 3:4:2, the molecular weight of polyethylene glycol is 1000, the amount ratio of prepolymer, 4-formylphenylboronic acid and 5A molecular sieve is 15mmo l:30mmo l:4g, and the model of polyoxymethylene is BS090.

[0056] The molar ratio of the modified prepolymer and ethylenediamine described in step A2 is 1:2, the amount of p-toluenesulfonic acid used is 1.5‰ of the mass of the modified prepolymer, the amount ratio of modified polyurethane, β-cyclodextrin and DMF is 1g:1g:10mL, and the molar ratio of isophorone diisocyanate, inclusion polyurethane and γ-aminopropyltriethoxysilane is 4:3:1.

[0057] The molar ratio of the modifier and the amino silicone described in step A3 is 14:1, and the mass ratio of the modified resin, the basalt fiber and the polyoxymethylene is 1:1:10.

[0058] The amino silicone is prepared by the following steps:

[0059] Step B1: Tetrahydrofuran, sodium hydroxide and deionized water are mixed uniformly, stirred and phenyltrimethoxysilane is added at a speed of 150 r / min and a temperature of 70°C, and the reaction is carried out for 6 hours, and then the tetrahydrofuran is removed, the substrate is dissolved in methanol, and acetic acid is added for neutralization to obtain an intermediate, and the intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane are mixed uniformly, and the reaction is carried out at a speed of 80 r / min and a temperature of 20°C for 25 hours to obtain a capping agent;

[0060] Step B2: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 110° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, a capping agent, chloroplatinic acid and DMF are mixed uniformly, and the reaction is carried out for 5 hours at a speed of 200 r / min and a temperature of 90° C. to obtain modified silicone;

[0061] Step B3: Dissolve the modified organosilicon in DMF, stir and add mixed acid at a speed of 80 r / min and a temperature of 5°C, react for 2 hours, adjust the pH value to neutral, and obtain nitroorganosilicon; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add nitroorganosilicon at a speed of 200 r / min and a temperature of 85°C, and react for 5 hours to obtain aminoorganosilicon.

[0062] The amount ratio of tetrahydrofuran, sodium hydroxide, deionized water and phenyltrimethoxysilane in step B1 is 200mL:70mmo l:3.5g:130mmo l, and the amount ratio of intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane is 1mmo l:1mL:1mmo l.

[0063] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step B2 is 2.4:2:3, the molar ratio of dihydrogenpolysiloxane and the capping agent is 1:1, and the amount of chloroplatinic acid used is 1‰ of the mass of dihydrogenpolysiloxane.

[0064] The amount ratio of the modified silicone and the mixed acid described in step B3 is 1g:6mL, the mixed acid is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 11:7, and the amount ratio of zinc powder, ammonium chloride, deionized water, DMF and nitro silicone is 2.5g:1g:20mL:50mL:1.5g.

[0065] Comparative Example 1: Compared with Example 1, the dopamine in step A1 is replaced by ethylenediamine, and the obtained product is used to replace the modified polyurethane, and the remaining steps are the same.

[0066] Comparative Example 2: Compared with Example 1, this comparative example uses modified polyurethane instead of inclusion polyurethane, and the remaining steps are the same.

[0067] Comparative Example 3: Compared with Example 1, this comparative example replaces the end-capping agent in step B2 with allyl alcohol, and replaces the amino silicone with the obtained product, and the remaining steps are the same.

[0068] The composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for tensile strength according to ISO 527-1:2019, with a tensile rate of 50 mm / min and a sample thickness of 4 mm. The notched impact strength was tested according to ISO 179-1:2000, with a sample thickness of 4 mm, a V-notch, a depth of 1 / 3 of the thickness, and a width of 2 mm. The test results are shown in Table 1 below.

[0069] Table 1

[0070]

[0071] It can be seen from the above table that the present application has good mechanical strength.

[0072] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-performance wear-resistant POM composite material, characterized in that: The specific steps include: Step A1: isophorone diisocyanate, polyethylene glycol and DMF are mixed and stirred, and dibutyltin dilaurate is added to react, and then dopamine is added to continue the reaction to obtain a prepolymer, and the prepolymer, 4-formylphenylboronic acid, 5A molecular sieve and DMF are mixed and reacted to obtain a modified prepolymer; Step A2: mixing and reacting the modified prepolymer, ethylenediamine, p-toluenesulfonic acid and DMF to obtain a modified polyurethane, mixing and stirring the modified polyurethane, β-cyclodextrin and DMF, and allowing to stand to obtain an inclusion polyurethane, mixing and reacting isophorone diisocyanate, the inclusion polyurethane and DMF, adding γ-aminopropyltriethoxysilane, and continuing the reaction to obtain a modifier; Step A3: The modifier, amino silicone and DMF are mixed and reacted to obtain a modified resin, and the modified resin, basalt fiber and polyoxymethylene are mixed and added into a twin-screw extruder, extruded and immersed in water for cooling to obtain a POM composite material.

2. The method for preparing a high-performance wear-resistant POM composite material according to claim 1, characterized in that: The molar ratio of isophorone diisocyanate, polyethylene glycol and dopamine in step A1 is 3:4:2, and the amount ratio of prepolymer, 4-formylphenylboronic acid and 5A molecular sieve is 15mmol:30mmol:4g.

3. The method for preparing a high-performance wear-resistant POM composite material according to claim 1, characterized in that: The molar ratio of the modified prepolymer and ethylenediamine described in step A2 is 1:2, the amount ratio of modified polyurethane, β-cyclodextrin and DMF is 1g:1g:10mL, and the molar ratio of isophorone diisocyanate, inclusion polyurethane and γ-aminopropyltriethoxysilane is n+1:n:1, where n is a natural number greater than 0.

4. The method for preparing a high-performance wear-resistant POM composite material according to claim 1, characterized in that: The molar ratio of the modifier and the amino silicone described in step A3 is 14:1, and the mass ratio of the modified resin, the basalt fiber and the polyoxymethylene is 1:1:

10.

5. The method for preparing a high-performance wear-resistant POM composite material according to claim 1, characterized in that: The amino silicone is prepared by the following steps: Step B1: tetrahydrofuran, sodium hydroxide and deionized water are mixed and stirred, and phenyltrimethoxysilane is added. After the reaction, the tetrahydrofuran is removed, the substrate is dissolved in methanol, and acetic acid is added for neutralization to obtain an intermediate. The intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane are mixed and reacted to obtain a capping agent; Step B2: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the mixture is reacted to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, a capping agent, chloroplatinic acid and DMF are mixed for reaction to obtain modified organosilicon; Step B3: Dissolve the modified organosilicon in DMF, stir and add mixed acid to react, adjust the pH value to neutral, and obtain nitroorganosilicon; mix zinc powder, ammonium chloride, deionized water and DMF, stir and add nitroorganosilicon to react, and obtain aminoorganosilicon.

6. The method for preparing a high-performance wear-resistant POM composite material according to claim 5, characterized in that: The amount ratio of tetrahydrofuran, sodium hydroxide, deionized water and phenyltrimethoxysilane in step B1 is 200mL:70mmol:3.5g:130mmol, and the amount ratio of the intermediate, tetrahydrofuran and γ-methacryloxypropyltrimethoxysilane is 1mmol:1mL:1mmol.

7. The method for preparing a high-performance wear-resistant POM composite material according to claim 5, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane in step B2 is 2.4:2:3, and the molar ratio of dihydrogenpolysiloxane and the capping agent is 1:

1.

8. The method for preparing a high-performance wear-resistant POM composite material according to claim 5, characterized in that: The amount ratio of the modified silicone and the mixed acid described in step B3 is 1g:6mL, the mixed acid is prepared by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 11:7, and the amount ratio of zinc powder, ammonium chloride, deionized water, DMF and nitro silicone is 2.5g:1g:20mL:50mL:1.5g.

9. A high performance wear-resistant POM composite material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.